Maintaining skin integrity in the aged: A systematic review. (March 2020) - Lichterfeld-Kottner, A.; El Genedy, M.; Lahmann, N.; Blume-Peytavi, U.; Büscher, A.; Kottner, J.
Abstract: Background: In aged nursing care receivers, the prevalence of adverse skin conditions such as xerosis cutis, intertrigo, pressure ulcers or skin tears is high. Adequate skin care strategies are an effective method for maintaining and enhancing skin health and integrity in this population. Objectives: The objective was to summarize the empirical evidence about the effects and effectiveness of non-drug topical skin care interventions to promote and to maintain skin integrity and skin barrier function in the aged, to identify outcome domains and outcome measurement instruments in this field. Design: An update of a previous systematic review published in 2013 was conducted. Data sources: Databases MEDLINE and EMBASE via OvidSP and CINAHL (original search January 1990 to August 2012, update September 2012 to May 2018) and reference lists were searched. Forward searches in Web of Science were conducted. Methods: A review protocol was registered in Prospero (CRD42018100792). Main inclusion criteria were primary intervention studies reporting treatment effects of basic skin care strategies in aged people with a lower limit of age range of 50 years and published between 1990 and 2018. Primary empirical studies were included with experimental study designs including randomized controlled trials and quasi-experimental designs. Methodological quality of included randomized controlled trials was evaluated using the Cochrane Collaboration's Tool for assessing risk of bias. Levels of evidence were assigned to all included studies. Results: Sixty-three articles were included in the final analysis reporting effects of interventions to treat and/or to prevent skin dryness, pruritus, general skin barrier improvement, incontinence-associated dermatitis, skin tears and pressure ulcers. Skin cleansers containing syndets or amphotheric surfactants compared with standard soap and water improved skin dryness. Lipophilic leave-on products containing humectants decreased skin dryness and reduced pruritus. Products with pH 4 improved the skin barrier. Application of skin protectants and structured skin care protocols decreased the severity of incontinence-associated dermatitis. Formulations containing glycerin and petrolatum reduced the incidence of skin tears. Thirty-five outcome domains were identified with nearly 100 different outcome measurement instruments. Conclusion: Included studies showed substantial heterogeneity regarding design, interventions and outcomes. Basic skin care strategies including low-irritating cleansers and lipophilic humectant-containing leave-on products are helpful for treating dry skin and improving skin barrier in the aged. Lower pH of leave-on products improves the skin barrier. The number of different outcome domains was unexpectedly high. We recommend to identify critical outcome domains in the field of skin care to make trial results more comparable in the future and to measure possible performance differences between different skin care strategies and products.